Hubungan Kadar Asam Urat Dengan Hipertrofi Ventrikel Kiri Pada Pasien Hipertensi Di Rsud Dr. Moewardi - Farmanda, Hanifah Rizki, Dr. Iin Novita Nurhidayati Mahmuda, M.Sc, Sp.PD (2017)
Background: Hypertension is a major public health problem. Until now, hypertension remains a major challenge in onesia. Control of hypertension has not been adequate though fective drugs widely available. One of the mplicationsofhypertension is left ventricular hypertrophy. Uric acid levels as a risk factor, plays an important role in the development of left ventricular hypertrophy in hypertensive patients. Objective: To knowing the correlation between uric acid levels with left ventricular hypertrophy in hypertensive patients in Dr. Moewardi General Hospital of Surakarta.Methods: The method used in this research is observational analytic with cross sectional approach. Data were taken from a sample of hypertensive patients in Dr. Moewardi General Hospital of Surakarta with purposive sampling technique. The data obtained are presented in tabular form, then analyzed using Chi-Square test at α = 0.05 level of significance. Result: The number of patients with left ventricular hypertrophy have high uric acid levels as much as 25 samples with a percentage of 83.3% of 30 patients, whereas in patients with left ventricular hypertrophy is not partial samples had normal uric acid levels as many as 15 samples with a percentage of 50.0% of the 30 patients. The results of the data analysis p = 0,006. Conclusion: There is a correlation between uric acid levels and left ventricular hypertrophy in hypertensive patients in Dr. Moewardi General Hospital of Surakarta. Keywords: Uric acid levels, left ventricular hypertrophy, hypertension